1978
DOI: 10.1002/ardp.19783110302
|View full text |Cite
|
Sign up to set email alerts
|

Potentiell antianaphylaktische 2′‐ und 6‐Carboxy‐flavonolderivate

Abstract: Für eine Struktur‐Wirkungs‐Untersuchung werden potentiell antianaphylaktisch aktive (PCA‐Test) 2′‐ und 6‐Carboxyflavonolderivate mit planarer Fixierung des B‐Rings ‐ 2‐substituierte 6,13‐Dehydropeltogynan‐11,14‐dione ‐ und mit nicht ebenem Molekülbau −6‐substituierte 2′‐Carboxyflanonole ‐ synthetisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…[7b,8, [22][23][24][25][26][27] The desired aminoflavones (i.e., 4) can be obtained by reduction or hydrolysis. The latter transformation usually requires harsh conditions (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…[7b,8, [22][23][24][25][26][27] The desired aminoflavones (i.e., 4) can be obtained by reduction or hydrolysis. The latter transformation usually requires harsh conditions (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report on the synthesis of 8-bromoflavone (6) starting from the commercially available 2-bromophenol (10) and its Buchwald-Hartwig reaction with some aliphatic and aromatic amine derivatives.…”
Section: Syn Thesismentioning
confidence: 99%
“…The esterification of 2-bromophenol (10) with acetyl chloride in the presence of triethylamine provided 2-bromophenyl acetate (9) in excellent yield (98%). After the first Fries rearrangement experiment of ester 9, which was carried out under the usual neat conditions, revealed that optimization is required because the reaction resulted exclusively in 3′-bromo-4′-hydroxyacetophenone (11) and only traces of the desired 3′-bromo-2′-hydroxyacetophenone (8) was formed (Scheme 3).…”
Section: Scheme 2 Retrosynthesis Of 8-bromoflavone (6)mentioning
confidence: 99%
See 1 more Smart Citation
“…In our search for antiasthmatic drugs we became therefore interested in the development of CysLT 1 receptor antagonists. , Our attempts to find new lead structures for CysLT 1 receptor antagonists started with the synthesis of carboxylated flavonoids, compounds which are known for their antianaphylactic properties. We found two new lead structures, 1 and 2 (Scheme ), which showed weak but significant affinities for the CysLT 1 receptor having K D values of 1.11 ± 0.14 × 10 -5 and 1.48 ± 0.28 × 10 -5 M, respectively.
2 Optimization of Lead Structure 1
…”
Section: Introductionmentioning
confidence: 99%